Hearing Protector Attenuation and Noise Exposure Among Metal Manufacturing Workers. Issue 3 (May 2019) - Sayler, Stephanie K.; Rabinowitz, Peter M.; Galusha, Deron; Sun, Kan; Neitzel, Richard L.
Abstract : Objectives: This study utilized personal noise measurements and fit-testing to evaluate the association between noise exposures and personal attenuation rating (PAR) values among participating workers, and second, to compare the attenuated exposure levels received by the workers and the British Standards Institute's recommended noise exposure range of 70 to 80 dBA. Design: We measured hearing protection device (HPD) attenuation among a sample of 91 workers at 2 US metal manufacturing facilities, through performance of personal noise dosimetry measurements and HPD fit-testing over multiple work shifts. We compared this testing with participant questionnaires and annual audiometric hearing threshold results. Results: The average 8-hr time-weighted average noise exposures for study participants was 79.8 dBA (SD = 7.0 dBA), and the average PAR from fit-testing was 20.1 dB (±6.7 dB). While differences existed between sites, 84% of the 251 PAR measurements resulted in effective protection levels below the recommended 70 dBA (indicating overprotection), while workers were underprotected (i.e., effective exposures >80 dBA) during <1% of monitored shifts. Our results also demonstrated a significant positive relationship between measured noise exposure and PAR among non–custom-molded plug users ( p = 0.04). Non–custom-molded plug wearers also showed a significant increase in PAR by sequential fit-test interaction ( p = 0.01), where on average, subsequent fit-testing resulted in increasingly higher HPD attenuation. Workers at site 1 showed higher PARs. PARs were significantly related to race, even when adjusting for site location. While age, hearing threshold level, task, and self-reported tinnitus showed no significant effect on individual PAR in an unadjusted model, site, race, and sand- or water-blasting activities were significant predictors in adjusted models. Within-worker variability in time-weighted averages and PARs across repeated measurements was substantially lower than variability between workers. Conclusions: Careful selection of HPDs is necessary to minimize instances of overprotection to workers in low and moderate occupational noise environments. The use of fit-testing in hearing conservation programs to evaluate PAR is recommended to avoid overprotection from noise exposure while also minimizing instances of under-attenuation.